Green Synthesis, Characterization and in vitro Antibacterial Studies of Gold Nanoparticles by Using Senna siamea Plant Seed Aqueous Extract at Ambient Conditions - Rajasekhar Reddy, G.; Bertie Morais, Antony; Nagendra Gandhi, N. (Asian Journal of Chemistry, 2013)
Biosynthesis of gold nanoparticles was achieved using chloroauric acid by aqueous extract of Senna siamea plant seed. Here, we reported the eco-friendly method for the preparation of gold nanoparticles in the presence of water, using aqueous extract of Senna siamea plant seed at room temperature. The aqueous extract of plant seed acts as a reducing and capping agents. The nanoparticle formation was confirmed by UV-visible spectroscopy and TEM images. The obtained gold nanoparticle was of triangular and hexagonal in shape. FTIR measurements were carried out to identify the possible biomolecules responsible for capping and efficient stabilization of the gold nanoparticles. The crystalline property was confirmed by X-Ray diffraction analysis. It is also verified that the efficacy of gold nanoparticles as a potential antibacterial agent and results obtained were well supported to our quest. Rapid and green synthesis methods using biological extracts have shown a great potential in nanoparticles synthesis protocols.